(3GdJbdjOjI , GdeSJMOKIs - (3YHO GdMejO(B, (3fSQjfs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2009)
(3GdJYQja HGdLQjeI GdGbJUGOjI , CSHGHgG JWhQgG h acQI gPg GdLQjeI aj GdJTQjYGJ GdeYGUQI h GdJMdjd Gdabgj h GdbVGFj dgG eY TQM GdLQGFe GdGbJUGOjI CQcGfgG GdeSDhdjI GdLfGFjI YfgG h GdGLQGAGJ h GdYbhHGJ ajgG ceG Je JfGhd GdLQGFe GdGbJUGOjI GdJbdjOjI HGdJWQb Gdi LQjeI GdJgQjH GdLeQcj , LQGFe bGfhf GdfbO , LQGFe GdTQcGJ , GdVQGFH , GdcSH ZjQ GdeTQhY , GdHfhc h GdGFJeGf h GdLQGFe HJRjja GdYedI h cPdc GdLQGFe GdGbJUGOjI GdeSJMOKI HGdJWQb Gdi NUhUjI GdLQjeI GdGbJUGOjI aj GdYGde GdKGdK h GdJMhdGJ GdGLJeGYjI efP eWdY GdSHYjfjGJ h bjeI GdcSH ZjQ GdeTQhY h GdSdhc GdhGbYj h cPdc LQGFe GdHfGA h GdGScGf , VQH GdSjGMI , JhXja GdGehGd , GdTjc h JGQjNg , GdfbGHGJ GdegfjI , GdMSGH GdBdj , ZSjd GdCehGd , ESGAI GSJYeGd GdSdWI GdGbJUGOjI h GdLQGFe GdeJYdbI HSjGSI GdGFJeGf (B.s
Keywords: (3GdGbJUGOs; (3GdLQGFe GdJLGQjIs; (3GdLQjeI h GdeLQehfs; (3LQGFe GdCehGds